2022
DOI: 10.3390/agronomy12112901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Nanoparticles (CS-NPs) on In Vitro Regeneration Response and Production of Potato virus Y (PVY)-Free Plants of Potato

Abstract: Potato virus Y (PVY) causes serious loss in the yield and quality of potatoes. The effect of chitosan nanoparticles (CS-NPs) on the regeneration response and production of PVY-free plants under in vitro conditions was studied. Murashige and Skoog (MS) medium supplemented with 0.1 mg L−1 Gibberellic acid (GA3), 0.1 mg L−1 Naphthalene acetic acid (NAA) and 500 mg L−1 malt extract was used for regeneration of plantlets from sprouts. Double Antibody Sandwich Enzyme-Linked Immunosorbent Assay (DAS-ELISA) and Revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Another concern for crop productivity is infection with virus, and potato virus Y (PVY) causes serious loss in the yield and quality of potatoes. Recently, to overcome this, Elsahhar et al [125] evaluated the role of CSNPs and suggested that their treatment proved effective in producing virus-free plants.…”
Section: Nps To Mitigate Stress and Virus Resistancementioning
confidence: 99%
“…Another concern for crop productivity is infection with virus, and potato virus Y (PVY) causes serious loss in the yield and quality of potatoes. Recently, to overcome this, Elsahhar et al [125] evaluated the role of CSNPs and suggested that their treatment proved effective in producing virus-free plants.…”
Section: Nps To Mitigate Stress and Virus Resistancementioning
confidence: 99%